2021
DOI: 10.3390/brainsci11091173
|View full text |Cite
|
Sign up to set email alerts
|

Pitch and Rhythm Perception and Verbal Short-Term Memory in Acute Traumatic Brain Injury

Abstract: Music perception deficits are common following acquired brain injury due to stroke, epilepsy surgeries, and aneurysmal clipping. Few studies have examined these deficits following traumatic brain injury (TBI), resulting in an under-diagnosis in this population. We aimed to (1) compare TBI patients to controls on pitch and rhythm perception during the acute phase; (2) determine whether pitch and rhythm perception disorders co-occur; (3) examine lateralization of injury in the context of pitch and rhythm percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 104 publications
(248 reference statements)
0
4
0
Order By: Relevance
“…In persons with TBI, perception of deviances in rhythmic sequences can be impaired as a result of the alteration in brain function due to the trauma caused by an external force 76 . Greater impairment in rhythmic perception is seen for patients with right hemisphere damage compared to the left hemisphere 76 . However, lesion location can highly impact possible processing difficulties of sounds.…”
Section: Discussionmentioning
confidence: 99%
“…In persons with TBI, perception of deviances in rhythmic sequences can be impaired as a result of the alteration in brain function due to the trauma caused by an external force 76 . Greater impairment in rhythmic perception is seen for patients with right hemisphere damage compared to the left hemisphere 76 . However, lesion location can highly impact possible processing difficulties of sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the abnormal expression of m 6 A-related proteins may lead to the development of various neurological diseases, such as PD [ 145 , 146 , 147 ], AD [ 148 , 149 , 150 , 151 , 152 ], MS [ 153 ], tumours [ 154 , 155 , 156 ], epilepsy [ 157 ], and neuropsychiatric disorders [ 158 ]. TBI, as one of the major diseases of CNS, often causes memory problems in humans [ 159 ]. Several CNS traumas, both in vitro and in vivo experimental systems [ 147 , 160 , 161 , 162 , 163 , 164 ], have demonstrated that m 6 A modification also plays important roles in the aetiology and pathogenesis of brain injuries.…”
Section: M 6 a Rna Modification And Bgamentioning
confidence: 99%
“…We did not perform the ROC analyses separately for the MTVD and neurological voice disorder groups and for the two musical background due to the small sample size of each subgroup. It may also be the case that the current NeAP protocol was not associated with optimal prediction ability given the number of tone pairs used (20) and the range of PD threshold. Smaller thresholds would probably be more likely to differentiate the groups with better sensitivity and/or specificity.…”
Section: Predictive Value Of Pd Testingmentioning
confidence: 99%
“…Given that the auditory cortex shows normal responses to pitch in this condition, the suggestion has been made that the impairments are due to reduced white matter functional connections between the auditory and inferior frontal cortices [19]. Traumatic brain injury is also known to affect pitch perception ability due to damages of the underlying pitch processing regions [20].…”
Section: Introductionmentioning
confidence: 99%